1997
DOI: 10.1520/jfs14161j
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death Due to Tricuspid Valve Myxoma with Massive Pulmonary Embolism in a 15-Month Old Male

Abstract: Myxomas of the tricuspid valve are extremely rare, with only 13 cases reported in the world literature (1). We report the case of a 15-month old male with tricuspid valve myxoma and massive myxomatous pulmonary emboli discovered at autopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Besides the possible disturbance of the heart activity due to the obstruction of a valve [15], bleedings and fragmentations can occur with subsequent embolism [1, 7, 12,16]. This seems more likely to occur in the left heart, probably because the higher pressures facilitate the fragmentation [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the possible disturbance of the heart activity due to the obstruction of a valve [15], bleedings and fragmentations can occur with subsequent embolism [1, 7, 12,16]. This seems more likely to occur in the left heart, probably because the higher pressures facilitate the fragmentation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the majority of the contributions is dealing with complications of inflammatory diseases [3,8], there still exists a considerable number of reports in relation to atherosclerosis [9,10]. More recently, there have also occurred reports with functional dysregulations [20,21] whilst sudden death due to primary heart tumours has been rarely reported [12,14,17,18] Primary cardiac tumours are a rare autopsy finding with a reported prevalence of 0.05% in autopsies [16]. Approximately 50% of them are atrial myxoma [11] that can be identified at the left (75%) or the right (25%) atrium [13].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, sporadic cases were instantly reported. Careful retrieval by the end of February 2008 had rendered a collection of 50 reported cases of tricuspid valve myxoma by 45 reports in world literature 1‐4,6‐46 . Of them, 34 (75.6%) articles were in English and 11 (24.4%) in non‐English with or without an English abstract.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions cause death by several mechanisms. Tumors of the heart cause sudden death by interfering with cardiac contractility, provoking lethal arrhythmias, or obstructing ventricular outflow [12,[39][40][41][42][43][44][45][46][47][48][49]. Lesions in the brain cause death by generating seizures, obstructing flow of cerebrospinal fluid, space-occupying hemorrhage, or invasion of the respiratory centers [11,15,[50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%